Depression, COVID-19 Anxiety, Subjective Well-being, and Academic Performance in University Students With COVID-19-Infected Relatives: A Network Analysis - Ventura-León, José; Caycho-Rodríguez, Tomás; Talledo-Sánchez, Karim; Casiano-Valdivieso, Kenia (Frontiers in Psychology, 2022)
This study aimed to examine the relationship between anxiety, depression, subjective well-being and academic performance in Peruvian university health science students with COVID-19 infected relatives. Eight hundred two university students aged 17 to 54 years (Mean 21.83; SD = 5.31); 658 females (82%) and 144 males (18%); who completed the Patient Health Questionnaire (PHQ-2), Coronavirus Anxiety Scale (CAS), Subjective Wellbeing Scale (SWB) and Self-reporting of Academic Performance (SAP) participated. A partial unregularized network was estimated using the ggmModSelect function. Expected influence (EI) values were calculated to identify the central nodes and a two-tailed permutation test for the difference between the two groups (COVID-19 infected and uninfected). The results reveal that a depression and well-being node (PHQ1-SWB3) presents the highest relationship. The most central nodes belonged to COVID-19 anxiety and there are no global differences between the comparison networks; but at the local level, there are connections in the network of COVID-19 infected students that are not in the group that did not present this diagnosis. It is concluded that anxious-depressive symptomatology and its relationship with well-being and evaluation of academic performance should be considered in order to understand the impact that COVID-19 had on health sciences students.